Preferensi makanan ikan pelangi arfak, Melanotaenia arfakensis Allen, 1990 di Sungai Nimbai dan Sungai Aimasi, Manokwari [Food preference of arfak rainbowfish, Melanotaenia arfakensis Allen, 1990 in Nimbai and Aimasi Streams, Manokwari] - Emmanuel Manangkalangi; M.F. Rahardjo; Djadja S. Sjafei; Sulistiono Sulistiono (Jurnal Iktiologi Indonesia, 2010)
The study of food preference of arfak rainbowfish (Melanotaenia arfakensis) in Nimbai and Aimasi streams, and Prafi river system were conducted from June to December 2007. Sampling was carried out monthly for seven months in four different habitat types, i.e. slow littoral, still littoral, pool, and run areas. Results showed that abundance of plankton and macroinvertebrate were found both in slow littoral and medium littoral, especially during low flow period (June to October). Macroinvertebrate that found naturally abundance are insect groups. Arfak rainbowfish are insectivorous, with preponderance index of stomach content during these periods are dominated by insect groups, i.e. Diptera, Ephemero-ptera, Coleoptera, and Trichoptera, so this species categorized as insectivorous. Also, electivity index showed a trend of food specification that naturally abundance. In order to maintain the population of arfak rainbowfish, conservation of their natural habitats is needed, especially riparian zone in channel of stream as its site of food source. AbstrakPenelitian preferensi makanan ikan pelangi arfak (Melanotaenia arfakensis) di Sungai Nimbai dan Aimasi di sistem Sungai Prafi dilaksanakan dari bulan Juni sampai Desember 2007. Pengambilan contoh dilakukan pada empat tipe habitat di dua lokasi penelitian, yaitu: bagian tepi beraliran lambat, bagian tepi beraliran sedang, lubuk, dan daerah beralir-an deras. Hasil penelitian memperlihatkan bahwa kelimpahan plankton dan makroavertebrata ditemukan pada tipe habitat beraliran lambat dan sedang pada saat kondisi debit air rendah (Juni-Oktober). Makroavertebrata yang ditemukan berlimpah adalah kelompok insekta. Ikan pelangi arfak adalah insektivora, terutama didominasi oleh kelompok insekta, ya-itu Diptera, Ephemeroptera, Coleoptera, dan Trichoptera. Indeks pilihan menunjukkan adanya kecenderungan pemilihan makanan yang terdapat dalam kondisi melimpah di perairan. Guna menjaga kelestarian ikan ini, konservasi habitat alaminya sangat diperlukan, terutama zona riparian yang merupakan tapak sumber daya makanannya.